2021
DOI: 10.1038/s41598-021-97987-w
|View full text |Cite
|
Sign up to set email alerts
|

Transcranial photobiomodulation and thermal stimulation induce distinct topographies of EEG alpha and beta power changes in healthy humans

Abstract: Our recent study demonstrated that prefrontal transcranial photobiomodulation (tPBM) with 1064-nm laser enables significant changes in EEG rhythms, but these changes might result from the laser-induced heat rather than tPBM. This study hypothesized that tPBM-induced and heat-induced alterations in EEG power topography were significantly distinct. We performed two sets of measurements from two separate groups of healthy humans under tPBM (n = 46) and thermal stimulation (thermo_stim; n = 11) conditions. Each gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
45
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(50 citation statements)
references
References 58 publications
3
45
0
2
Order By: Relevance
“…With the same inclusion and exclusion criteria as those in our previous studies ( Wang et al, 2016 , 2018 , 2021 ), a total of 49 healthy human subjects were recruited (19 females of 27.4 ± 6.1 years of age; 30 males of 28.7 ± 4.7 years of age) from the local community of the University of Texas at Arlington for participating this study. The experimental protocol was approved by the institutional review board (IRB) at the University of Texas at Arlington and complied with all applicable federal and NIH guidelines.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…With the same inclusion and exclusion criteria as those in our previous studies ( Wang et al, 2016 , 2018 , 2021 ), a total of 49 healthy human subjects were recruited (19 females of 27.4 ± 6.1 years of age; 30 males of 28.7 ± 4.7 years of age) from the local community of the University of Texas at Arlington for participating this study. The experimental protocol was approved by the institutional review board (IRB) at the University of Texas at Arlington and complied with all applicable federal and NIH guidelines.…”
Section: Methodsmentioning
confidence: 99%
“…The sham-controlled experimental protocol was reported earlier ( Wang et al, 2021 ) but briefly shown in Figure 1 . Each tPBM or sham experiment took a total of 13 min, ranging from −2 min to 11 min, with a 2-min baseline, an 8-min tPBM/sham, and a 3-min recovery period.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The mechanisms of PBM are still under debate, but are possibly related to mitochondrial enzymes, the production of reactive oxygen species, and endogenous red light-sensing proteins ( Hamblin, 2016 ). Outside of different survival pathways, transcranial PBM has been shown to modulate neural activity, which was apparent through changes in electroencephalography (EEG) even in humans ( Zomorrodi et al, 2019 ; Wang et al, 2021 ). To summarize, the effects of both endogenous opsin activity (induced by blue light) and PBM (induced by red light) need to be considered in each study.…”
Section: Red Versus Bluementioning
confidence: 99%
“…The study concluded that neural responses in different EEG frequency bands were sensitive to different factors when thermally stimulating subjects’ hands. Furthermore, the study by Wang et al 21 studied changes in EEG rhythms, after laser-induced heat thermal stimulation of 33–41 C. The authors reported a decrease in EEG power topographic patterns as a result of the laser-induced heat stimulation. In another study by Breton et al 22 , they focused on power modulation of different oscillatory components and its sensitivity to thermal comfort variations using EEG recordings.…”
Section: Introductionmentioning
confidence: 99%